Blockade of Fibroblast YAP Attenuates Cardiac Fibrosis and Dysfunction Through MRTF-A Inhibition - Francisco, Jamie; Zhang, Yu; Jeong, Jae Im; Mizushima, Wataru; Ikeda, Shohei; Ivessa, Andreas; Oka, Shinichi; Zhai, Peiyong; Tallquist, Michelle D.; Del Re, Dominic P. (JACC. Basic to translational science, 2020)
[Display omitted] •YAP is activated by myocardial infarction or neuroendocrine stimulation in cardiac fibroblasts.•Active YAP promotes TEA domain transcription factor-1–mediated transcription of myocardin-related transcription factor A to facilitate cardiac myofibroblast differentiation and extracellular matrix gene expression.•Cardiac fibroblast YAP knockout mice have attenuated cardiac fibrosis and dysfunction in response to myocardial infarction. Fibrotic remodeling of the heart in response to injury contributes to heart failure, yet therapies to treat fibrosis remain elusive. Yes-associated protein (YAP) is activated in cardiac fibroblasts by myocardial infarction, and genetic inhibition of fibroblast YAP attenuates myocardial infarction–induced cardiac dysfunction and fibrosis. YAP promotes myofibroblast differentiation and associated extracellular matrix gene expression through engagement of TEA domain transcription factor 1 and subsequent de novo expression of myocardin-related transcription factor A. Thus, fibroblast YAP is a promising therapeutic target to prevent fibrotic remodeling and heart failure.